Killdeer nest - Lindquist, Mark, photographer (Colorado State University. Libraries, 2001)
Newly-hatched killdeer and three eggs in nest on SGS (date field probably indicates when photo was uploaded).
Keywords: eggs; nest; SGS; killdeer; birds